A Note On The New Record Of The Reptile Fauna In Pulau Tinggi, Johor, Malaysia - Yin Hui Ng; Md-Zairi Zainal; Muhammad Abu Bakar Abdul-Latiff; Ehwan Ngadi (universiti malaysia terengganu, 2024)
Indexed by SCOPUS/ERA/MYCITE